Volatility spillovers and comparative analysis of conventional and Islamic equity markets during Global Financial Crisis and COVID-19 pandemic: empirical evidence from Malaysia - Foo, Siong Min; Ab Razak, Nazrul Hisyam; Kamarudin, Fakarudin; Zakaria, Nadisah (Universiti Putra Malaysia, 2025)
This study investigates the co-movement and integration between conventional and Islamic indexes in Malaysia by analysing the volatility spillover and asymmetric effect over the period of 28/2/2007 to 28/2/2023. The sample is divided into five periods: full sample period, pre-, during- and post-Global Financial Crisis period including the during-COVID-19 period. Based on GARCH-M and EGARCH models, the findings indicate that the volatility of every index is more responsive to its lag values than it is to new shocks with the Islamic index consistently demonstrating higher volatility persistence than its conventional counterpart. The EGARCH results also observe asymmetric bidirectional volatility spillovers between Malaysia’s conventional and Islamic index in the during-GFC period. However, unidirectional volatility spillover is found in every sample period, except for the during-COVID-19. This indicates the absence of return and volatility spillover, which makes COVID-19 a special/unique event for Malaysia. The overall findings support the decoupling hypothesis for Malaysian conventional and Islamic indexes. Hence, it is important for policymakers in developing policies to deal with the co-movement and spillovers of the indexes for achieving financial stability. This study suggests that domestic investors in Malaysia have high diversification opportunities by combining both conventional and Islamic indexes in their portfolios in the long run.